Determinants of domestic violence against women in Cambodia: How digital access, media exposure, motorcycle ownership, and partners’ alcohol use matter - Samnang Um; Sopheap Suong; Chantrea Sieng; Sovandara Heng; Grace Marie Ku; Sothy Heng (PLoS ONE, 2026)
Domestic violence against women remains a public health and socio-economic burden in Cambodia, with only slow declines over the past two decades. This study examined how digital access, media exposure, motorcycle ownership, and partners’ alcohol use are associated with intimate partner violence (IPV), defined as the experience of any sexual, physical, or emotional violence by a current or former partner within the past 12 months, adjusted for socio-demographic factors. A cross-sectional analysis of 5,780 weighted women aged 15–49 from the 2021–2022 Cambodia Demographic and Health Survey. IPV was regressed on mobile phone ownership, internet use, media exposure, motorcycle ownership, and partners’ alcohol use using survey-adjusted multivariable logistic models. Overall, 13.2% of women reported experiencing IPV in the past year, specifically emotional violence (12.2%), physical violence (4.4%), and sexual violence (1.9%). Smartphone ownership was associated with lower odds of emotional violence (AOR = 0.7; 95% CI 0.5–0.9) and IPV (AOR = 0.7; 95% CI: 0.5–1.0), whereas low-frequency internet use predicted higher odds of emotional violence (AOR = 1.7; 95% CI: 1.1–2.7) and IPV (AOR = 1.6; 95% CI: 1.1–2.5). Partner alcohol use was a strong risk factor for IPV (AOR = 3.0; 95% CI: 2.1–4.1 and all forms: sexual (AOR = 3.5; 95% CI: 1.1–11.4), physical (AOR = 5.6; 95% CI: 2.8–11.5), and emotional (AOR = 3.1; 95% CI: 2.2–4.4). Women in wealthier households had significantly lower odds of IPV (AOR = 0.6; 95% CI: 0.5–0.8), and specifically, physical violence (AOR = 0.4; 95% CI: 0.3–0.7). These findings highlight the dual role of digital inclusion—smartphones may enhance women’s protection, while limited or monitored internet access could heighten risk. Policies should be formulated to prioritize safe and private digital access, integrate gender-sensitive digital literacy, and strengthen alcohol control, and women’s economic empowerment within Cambodia’s National Action Plan to Prevent Violence Against Women 2019–2023 and forthcoming 2024–2030 framework.